Hubungan Negara dan Otoritas Agama dalam Pengawasan Penerapan Syariah di Indonesia - Zuhdi, Achmad; Saputra, Edi; Hidayat, Hasannudin; Umam, Khoirul; Hayamansyah, Didi (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This study examines the functional relationship and institutional conflict between religious authorities namely the National Sharia Council of the Indonesian Ulema Council (DSN MUI) and the Sharia Supervisory Board (DPS) and state authorities, particularly the Financial Services Authority (OJK), in supervising sharia compliance within Indonesia’s financial institutions. Employing a normative-qualitative method with a statutory and conceptual approach, the research analyzes relevant laws, DSN fatwas, OJK regulations, as as well as a conceptualized model derived from legal approaches and public management theory. The findings reveal a structural gap: DSN MUI’s fatwas significantly influence regulatory practice yet lack formal legal force, while OJK, despite its regulatory mandate, cannot substantively review those fatwas. Moreover, DPS appointments by financial institutions raise concerns about independence and public accountability. As a scholarly contribution, this study introduces the Integrated Sharia Governance Framework (ISGF), a model that proposes procedural integration between DSN MUI and OJK, strengthens DPS oversight, and embeds fatwas into formal regulatory processes without eroding religious autonomy. The ISGF serves as a normative solution to institutional fragmentation and offers a context-sensitive approach to harmonizing religious authority with democratic rule-of-law principles in Indonesia’s sharia financial governance